Physiographic characterization of the municipality of Garanhuns –PE - Costa, Samuel Othon de Souza; Ramos, Renilson Pinto da Silva; Deus, Rodolfo Alexandre da Silva Gomes de; Silva, Suzana de Araújo; Gomes, Daniel Dantas Moreira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The present work, perform a search physiographic characterization of the municipality of Garanhuns, Pernambuco, there is a distance of 228 km from the capital, Recife. In developing the survey was used GIS techniques to consolidate the results obtained. To conduct the study used data from Digital Elevation Models, the SRTM (Shuttle Radar Topography Mission) and satellite images of Landsat 8 Software ArcGIS 10 2 2 was used for the processing of digital images. To achieve the results, was also employed data from going to the field of study for proof of data from satellite images and collecting information. However the location was drawn figures, altimetry, topographic, relief shading, orientation of slopes and foreclosure relief, the municipality of Garanhuns for representation.